2023
DOI: 10.1007/s00401-023-02583-z
|View full text |Cite
|
Sign up to set email alerts
|

Brain DNA methylomic analysis of frontotemporal lobar degeneration reveals OTUD4 in shared dysregulated signatures across pathological subtypes

Abstract: Frontotemporal lobar degeneration (FTLD) is an umbrella term describing the neuropathology of a clinically, genetically and pathologically heterogeneous group of diseases, including frontotemporal dementia (FTD) and progressive supranuclear palsy (PSP). Among the major FTLD pathological subgroups, FTLD with TDP-43 positive inclusions (FTLD-TDP) and FTLD with tau-positive inclusions (FTLD-tau) are the most common, representing about 90% of the cases. Although alterations in DNA methylation have been consistentl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 107 publications
0
5
0
Order By: Relevance
“…This enzyme has not been previously associated with FTD; however, ubiquitin‐dependent signaling is a well‐known disease‐related process in several neurodegenerative disorders, contributing to protein degradation, regulation of neuronal function, and inflammation 60 . A recent study of brain methylation in symptomatic postmortem FTLD has also identified differential methylation of a deubiquinating enzyme ( OTUD4 ), postulating a role for methylation in key disease processes such as ubiquitin signaling 38 . Therefore, TSS hypermethylation in the presymptomatic group may indicate the occurrence of disease‐associated mechanisms at this stage.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This enzyme has not been previously associated with FTD; however, ubiquitin‐dependent signaling is a well‐known disease‐related process in several neurodegenerative disorders, contributing to protein degradation, regulation of neuronal function, and inflammation 60 . A recent study of brain methylation in symptomatic postmortem FTLD has also identified differential methylation of a deubiquinating enzyme ( OTUD4 ), postulating a role for methylation in key disease processes such as ubiquitin signaling 38 . Therefore, TSS hypermethylation in the presymptomatic group may indicate the occurrence of disease‐associated mechanisms at this stage.…”
Section: Discussionmentioning
confidence: 99%
“… 60 A recent study of brain methylation in symptomatic postmortem FTLD has also identified differential methylation of a deubiquinating enzyme ( OTUD4 ), postulating a role for methylation in key disease processes such as ubiquitin signaling. 38 Therefore, TSS hypermethylation in the presymptomatic group may indicate the occurrence of disease‐associated mechanisms at this stage. At the same time, presymptomatic carriers showed gene body methylation (suggesting gene upregulation) of genes involved in neuronal cellular processes when compared to symptomatic carriers, including the TARDBP and the PRKAR1B genes, both associated with FTD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although PD is primarily considered to be a grey matter disease, recent transcriptomic studies have revealed an upregulation in oligodendrocyte-related genes in the brain, a downregulation in the myelin genes and the oligodendrocyte development pathway in the cingulate cortex, and a loss of oligodendrocytes in post-mortem midbrain tissue in PD patients [69]. Conversely, PSP is characterized by abnormal tau protein aggregation in both grey and white matter regions, and single-nucleus RNA sequencing in the subthalamic nucleus of PSP identified specific contributions of the glial cell-types including increased EIF2 signalling, in addition to dysregulation in genes and pathways related to apoptotic regulation and autophagy signalling in astrocytes and oligodendrocytes [18, 67]. As in the case of MSA, bulk transcriptomic analysis also revealed changes in gene expression of myelin-related genes in PSP [3].…”
Section: Introductionmentioning
confidence: 99%